PENGARUH MODAL KERJA, PERPUTARAN KAS, DAN ARUS KAS TERHADAP CURRENT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Stevanie Clorin; Mitan Hardika; Surya Rahmat Prayoga; Enda Noviyanti; Hottua Samosir; Andhy Stephanus (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
This research is meant to find out the effects of working capital, cash turnover, and cash flow on the current ratio of manufacture companies which are listed in Indonesia Stock Exchange (IDX) in 2013-2016 periods both simultaneous and partial and to find out which one of these independent variables that significant effects to the current ratio of manufacture companies which are listed in Indonesia Stock Exchange. Research data tested with testing classical assumptions and use multiple linear regression analysis. The results showed that the variable working capital has positive and significant effects, cash turnover and cash flow have negative and significant effects on the current ratio in manufacturing companies which are listed in the Indonesian capital market in the 2013-2016 periods.